2004
DOI: 10.1177/009145090403100207
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Substance Use among Young People: Findings of a Multi-Center Study in Three African Countries

Abstract: This paper presents the findings of baseline assessments on psychoactive substance use that were conducted in selected sites in South Africa, Tanzania and Zambia between December 2000 and September 2001. The assessments focused on the status of substance use and prevention resources. They showed that a wide range of substances were used—especially alcohol, tobacco and painkillers—and included substances taken by injection. Usage was particularly widespread in settings where trade in substances offered a means … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 6 publications
2
22
1
Order By: Relevance
“…The findings of the study indicated the highest use of alcohol among the young people in South Africa (88%), followed by Zambia (47%) and Tanzania (18%). The percentages of use within the last thirty days and the last year were also highest for South Africa (38% & 69%), followed by Zambia (19% & 34%) and Tanzania 15% & 15%).In contrast to the previous findings by Alao et al (2004), Nkowane et al (2004) reported the youngest age of the first alcohol consumption as 10 years. Studies from the South African and Zambian samples reported the first alcohol consumption age range from 10 to 14 years, which was accounted for by 37% of the South African sample and 47% of the Zambian sample.…”
Section: Introductioncontrasting
confidence: 65%
See 1 more Smart Citation
“…The findings of the study indicated the highest use of alcohol among the young people in South Africa (88%), followed by Zambia (47%) and Tanzania (18%). The percentages of use within the last thirty days and the last year were also highest for South Africa (38% & 69%), followed by Zambia (19% & 34%) and Tanzania 15% & 15%).In contrast to the previous findings by Alao et al (2004), Nkowane et al (2004) reported the youngest age of the first alcohol consumption as 10 years. Studies from the South African and Zambian samples reported the first alcohol consumption age range from 10 to 14 years, which was accounted for by 37% of the South African sample and 47% of the Zambian sample.…”
Section: Introductioncontrasting
confidence: 65%
“…Another study by Nkowane, Rocha-Silva, Saxena, Mbatia, Ndubani and Wier-Smith (2004) investigated psychoactive substance use among young people in South Africa, Tanzania and Zambia (age [10][11][12][13][14][15][16][17][18][19][20][21]. The sample for the study was drawn from both rural and urban populations and it included participants from a college, a mental health center, and a human services research council.…”
Section: Introductionmentioning
confidence: 99%
“…Lifetime alcohol use among 15 to 21 year old Zambian youth was found to be approximately 50% (Magnani, Karim, Weiss, Bond, Lemba, 2002), marijuana use was 86%, and inhalant usage was 47% (Nkowane et al, 2004), which is similar to rates found among homeless and street youth in the United States (Bousman et al, 2005). Moreover, the use of alcohol is also associated with using other drugs (Peltzer, 2009).…”
Section: Introductionsupporting
confidence: 54%
“…In addition, marijuana use increases youths’ chances of engaging in sex as found in a study of Zambian in-school adolescents (Siziya, Muula, Kazembe, & Rudatsikira, 2008). Finally, research also finds that youth often use drugs to enhance sexual experiences (Magnani et al, 2002; Nkowane et al, 2004; Peltzer, 2009), suggesting that substance use and risky sexual behaviors are inextricably linked (Siziya et al, 2008). This linkage is further evidenced by the fact that the median age of first alcohol use is 15, which coincides with the median age of first sexual experience (Magnani et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation